ISL1 controls pancreatic alpha cell fate and beta cell maturation - Bohuslavova, Romana; Fabriciova, Valeria; Lebrón-Mora, Laura; Malfatti, Jessica; Smolik, Ondrej; Valihrach, Lukas; Benesova, Sarka; Zucha, Daniel; Berkova, Zuzana; Saudek, Frantisek; Evans, Sylvia M; Pavlinkova, Gabriela (Cell & bioscience, 2023)
BACKGROUND: Glucose homeostasis is dependent on functional pancreatic α and ß cells. The mechanisms underlying the generation and maturation of these endocrine cells remain unclear. RESULTS: We unravel the molecular mode of action of ISL1 in controlling α cell fate and the formation of functional ß cells in the pancreas. By combining transgenic mouse models, transcriptomic and epigenomic profiling, we uncover that elimination of Isl1 results in a diabetic phenotype with a complete loss of α cells, disrupted pancreatic islet architecture, downregulation of key ß-cell regulators and maturation markers of ß cells, and an enrichment in an intermediate endocrine progenitor transcriptomic profile. CONCLUSIONS: Mechanistically, apart from the altered transcriptome of pancreatic endocrine cells, Isl1 elimination results in altered silencing H3K27me3 histone modifications in the promoter regions of genes that are essential for endocrine cell differentiation. Our results thus show that ISL1 transcriptionally and epigenetically controls α cell fate competence, and ß cell maturation, suggesting that ISL1 is a critical component for generating functional α and ß cells.
Keywords: Pancreas development; Transcriptome; Epigenetic histone modification; Pancreatic endocrine cells